Artificial intelligence versus human news anchors: Trust in the age of AI - Breviglieri, F.; Guerreiro, J. M.; Loureiro, S. (Journal of Marketing Communications)
The increasing use of artificial intelligence (AI) has raised questions about the technology and its potential applications. Among the possibilities, personalised news technology emerges as an alternative to traditional media. This study investigates the levels of trust people demonstrate in AI-generated news anchors compared to human presenters. A total of 306 respondents participated in an online experiment. Of these, 152 were randomly assigned to view an AI-generated news anchor accompanied by a description of the personalised news technology, while the remaining 154 watched the same video presented by a human presenter, with no mention of personalisation. A PLS-SEM analysis was employed to test the hypotheses of this research. The results reveal similar levels of trust between viewers of the AI-generated news anchor and those of the human presenter. The main conclusion of this investigation is that AI-generated content can be potentially trustworthy for users.